2020
DOI: 10.1038/s41598-020-68873-8
|View full text |Cite
|
Sign up to set email alerts
|

Nano-scale depth-varying recrystallization of oblique Ar+ sputtered Si(111) layers

Abstract: Silicon, the workhorse of semiconductor industry, is being exploited for various functional applications in numerous fields of nanotechnology. In this paper, we report the fabrication of depth controllable amorphous silicon (a-Si) layers under 80 keV Ar + ion sputtering at off-normal ion incidences of 30°, 40° and 50° and crystallization of these amorphous Si(111) layers under thermal annealing. We find that the irradiated samples were not fully amorphized even for the lowest oblique incidence of 30°. Sputteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…43 Also a previous study on UO 2 film showed that its oxidation (into UO 2+x ) leads to less defined U 4f satellite intensity peaks. 45 Conversely, sample annealing, which restores the crystal order, 46 intensifies the satellite peaks. 46 In the present case by oxidation, the plasma alters the initial fluorite structured UO 2 into layer structured UO 3 .…”
Section: Dalton Transactions Papermentioning
confidence: 99%
See 1 more Smart Citation
“…43 Also a previous study on UO 2 film showed that its oxidation (into UO 2+x ) leads to less defined U 4f satellite intensity peaks. 45 Conversely, sample annealing, which restores the crystal order, 46 intensifies the satellite peaks. 46 In the present case by oxidation, the plasma alters the initial fluorite structured UO 2 into layer structured UO 3 .…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…45 Conversely, sample annealing, which restores the crystal order, 46 intensifies the satellite peaks. 46 In the present case by oxidation, the plasma alters the initial fluorite structured UO 2 into layer structured UO 3 . This process destroys crystal order.…”
Section: Dalton Transactions Papermentioning
confidence: 99%